2015
DOI: 10.3389/fpsyg.2015.00300
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical substrates for the volitional regulation of heart rate

Abstract: The control of physiological arousal can assist in the regulation of emotional state. A subset cortical and subcortical brain regions are implicated in autonomic control of bodily arousal during emotional behaviors. Here, we combined human functional neuroimaging with autonomic monitoring to identify neural mechanisms that support the volitional regulation of heart rate, a process that may be assisted by visual feedback. During functional magnetic resonance imaging (fMRI), 15 healthy adults performed an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…65,66 Across studies, both left and right sided activity changes have been reported, consistent with the lack of lateralized effects seen here with acute stimulation. While other regions, including the anterior insula and frontal cortex are clearly critical to a full interoceptive experience and a complete recovery from depression, 67 the common involvement of the cingulate in both the Type 1 ‘Salient’ and Type 2 ‘Best’ response types is nonetheless consistent with this principal role of the cingulate in interoceptive processing.…”
Section: Discussionmentioning
confidence: 78%
“…65,66 Across studies, both left and right sided activity changes have been reported, consistent with the lack of lateralized effects seen here with acute stimulation. While other regions, including the anterior insula and frontal cortex are clearly critical to a full interoceptive experience and a complete recovery from depression, 67 the common involvement of the cingulate in both the Type 1 ‘Salient’ and Type 2 ‘Best’ response types is nonetheless consistent with this principal role of the cingulate in interoceptive processing.…”
Section: Discussionmentioning
confidence: 78%
“…Neural activity in the opercular cortex (with anterior insula) is linked to cardiac interoception ( Critchley et al, 2004 ). Moreover, biofeedback-guided control of heart rate is associated with activation of the frontal pole ( Jones et al, 2015 ). These previous observations suggest our finding may recruitment of these regions for down-regulation of cardiac arousal by negative worrisome thoughts in patients with GAD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also observed that the obese participants had lower BL CMRglu in left DLPFC. We speculate that obese participants have greater difficulty in suppressing their desire to eat during food stimulation, for it is a more demanding cognitive effort that appears to require a greater energetic cost for activating the pgACC/caudate region which is needed for self-regulation [35].…”
Section: Fig 4 Correlation Between Changes In the Behavioral Measurementioning
confidence: 99%